Gender differences in cognitive functions of youth water polo players - Kovacevic, N.; Mihanovic, F.; Kalcina, L. L.; Matijaš, T.; Rukavina, I.; Galic, T. (SportMont, 2024)
Water polo (WP) as a highly demanding contact team sport, requires from players to have well developed cognitive functions, similar as in other team sports. Following same rules for females and males it is important to realize differences between them, which may contribute to their sports success and help coaches to develop adequate training models. Therefore, the aim of this study was to compare cognitive functions between female and male youth WP players. There were 36 female (25%) and 106 male (75%) youth WP players aged 12 to 14 years enrolled in this study. Variables measured included anthropometric indices, specific functional swimming capacities and cognitive functions testings using the Stroop test. Females showed better psychomotor speed (Stroop Off) (females 61.79±6.79 s vs. males 64.83±8.31 s, p=0.048) and response inhibition (Stroop On) (females 73.44±10.74 s vs. males 78.67±14.82 s, p=0.025) than males. Female youth WP players showed better results in psychomotor speed, inhibitory control and motor speed compared to males, taking both age and gender into account. Such differences might be of interest for coaches in WP, as well as in different sports to help them develop appropriate training strategies for each athlete.